Gastric cancer epidemiology from 2009 to 2019 in Dnipro Region, Ukraine. (February 2023) - Semenov, Viktor V.; Kriachkova, Lilia V.; Shestakova, Natalia; Khanov, Viktor; Donchenko, Halyna; Balashova, Olga; Viklienko, Yulia I.
Abstract: Background: Gastric cancer (GC) is in top-five the most frequent cancers in Ukrainian males and is the third cause of death among patients with cancer. GC keeps its leading position in cancer ranks despite the decline in incidence and mortality over the last 50 years. Local epidemiological information will help in better targeting medical and public health interventions. Patients and methods: The data about 8438 patients with newly diagnosed GC between 2009 and 2019 was obtained from Dnipro Cancer Registry. Results: Incidence decreased from 24.5 to 22.6, mortality decreased from 21.4 to 15.7 (per 100000), death rate increased from 0.64 to 1.04 between 2009 and 2019. Over 11 years of observation incidence was 23.4, mortality was 19.4, death rate was 0.721. Standardised incidence ratio was 1.42, standardised mortality rate was 1.67; age-standardised incidence was 25.5, age-standardised mortality was 21.2 (European standard). Median (95% confidence interval (95% CI)) survival of the patients was 172 (165−178) days. One-year survival rate fluctuated between 27% and 34%. Male sex and older age were associated with higher risk of death (hazard ratio (95% CI) – 1.08 (1.03–1.13) vs females and 1.15 (1.12–1.17) per 10-years increase of age, respectively). Conclusions: The study describes the trends in epidemiology of gastric cancer in Dnipro region, Ukraine, between 2009 and 2019. The need for the national prevention strategy of GC in Ukraine was identified.